2016
DOI: 10.2298/abs150630025a
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among Fusarium graminearum and F. culmorum isolates based on ISSR markers

Abstract: To characterize the isolates of F. graminearum and F. culmorum fungi from Turkey and Iran, we performed ISSR analysis with 18 non-anchored and 23 anchored (including ten novel) primers. Amplification product sizes were 0.2-3.5 kb. In total, 405 bands were scored, 24 of which (5.92%) were polymorphic. The similarities among F. graminearum isolates were calculated as 62.3-99%, and among F. culmorum as 65.7-94.3%. Moderate genetic variation at intra- and inter-specific levels was determined, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
3
8
0
4
Order By: Relevance
“…In addition, Mishra et al (2003) found a high degree of intra-specific polymorphism among F. culmorum isolates using inter-simple sequence repeat (ISSR) analysis. Albayrak et al (2016) also studied the relationship between Fusarium isolates according to their species and geographic regions by using ISSR markers. In another study, Bayraktar and Fatma (2010) found that ISSR markers have a high degree of intra- and interspecific polymorphisms among Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Mishra et al (2003) found a high degree of intra-specific polymorphism among F. culmorum isolates using inter-simple sequence repeat (ISSR) analysis. Albayrak et al (2016) also studied the relationship between Fusarium isolates according to their species and geographic regions by using ISSR markers. In another study, Bayraktar and Fatma (2010) found that ISSR markers have a high degree of intra- and interspecific polymorphisms among Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, parasexual status is suggested by Miedaner et al (2001Miedaner et al ( , 2008. This suggestion was also supported by mating type analysis by location of two idiomorphic alleles on a single isolates genome (Obanor et al, 2010(Obanor et al, , Çepni et al, 2013Albayrak et al, 2016).…”
Section: Introductionmentioning
confidence: 88%
“…Several strategies including random amplified polymorphic DNA, inter simple sequence repeats and simple sequence repeats, have been currently used in F. culmorum genotyping (Miedaner et al, 2001;Gurel et al, 2010;Irzykowska et al, 2013;Albayrak et al, 2016). Sequence related amplified polymorphism (SRAP) method uses two primers with nucleotide sequence of conserved coding sites throughout the genomes.…”
Section: Introductionmentioning
confidence: 99%
“…Las estrategias clásicas para el estudio de la variabilidad genética tales como anatomía comparativa, morfología, embriología y fisiología se han visto complementadas en gran medida por técnicas moleculares basadas en los polimorfismos de ADN o de proteínas (Doyle y Doyle, 1987;González y Simpson, 1997;Vega-Ramos et al, 2013), recientemente aplicadas en Fusarium de cereales (Albayrak et al, 2016;Consolo et al, 2015). Por tal motivo el objetivo del presente estudio fue caracterizar e identificar molecularmente y evaluar la patogenicidad de las especies de Fusarium asociadas al amarillamiento o madurez prematura en el cultivo de trigo en el sur del Bajío guanajuatense.…”
Section: Caracterización Molecular Y Patogénesis De Fusariumunclassified